Brainstem Correlates of a Cold Pressor Test Measured by Ultra-High Field fMRI - Hendriks-Balk, Mariëlle C.; Megdiche, Fatma; Pezzi, Laura; Reynaud, Olivier; Da Costa, Sandra; Bueti, Domenica; Van De Ville, Dimitri; Wuerzner, Grégoire (Frontiers in Neuroscience, 2020)
Modern imaging techniques such as blood oxygen level-dependent (BOLD) functional magnetic resonance imaging (fMRI) allow the non-invasive and indirect measurement of brain activity. Whether changes in signal intensity can be detected in small brainstem regions during a cold pressor test (CPT) has not been explored thoroughly. The aim of this study was to measure jointly whole brain and brainstem BOLD signal intensity changes in response to a modified CPT. Methods: BOLD fMRI was measured in healthy normotensive participants during unblinded a randomized crossover study (modified CPT vs. control test) using ultra-high field 7 Tesla MRI scanner. Data were analyzed using Statistical Parametric Mapping (SPM) in a whole-brain approach, and with a brainstem-specific analysis using the spatially unbiased infra-tentorial template (SUIT) toolbox. Blood pressure (BP) and hormonal responses (norepinephrine and epinephrine levels) were also measured. Paired t-test statistics were used to compare conditions. Results: Eleven healthy volunteersparticipants (6 womanwomen, mean age 28 ± 8.9 years) were enrolledanalyzed after giving written, informed consent. Mean arterial BP increased from 834 ± 121 mm Hg to 876 ± 12 mm Hg (p=0.00974) during the CPT. Whole-brain analysis revealed significant activations linked to the CPT in the right supplementary motor cortex, midcingulate (bilateral) and the right anterior insular cortex. The brainstem-specific analysis showed significant activations in the dorsal medulla. Conclusions: Changes in BOLD fMRI signal intensity in brainstem regions during a CPT can be detected, and show an increased response during a cold stress in healthy volunteers. Consequentlyvolunteers. Consequently, BOLD fMRI at 7T is a promising tool to explore and acquire new insights in the comprehension of neurogenic hypertension.